(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the disease structure of patients participating in health insurance for medical examination and treatment at Thanh Oai General Hospital, Hanoi, from 2019 to 2023. Research methods: Secondary data analysis based on the hospital’s annual statistical report. Results: Annually, the number of patients with health insurance cards ranged from 65,000 to 92,000, diagnosed according to the ICD-10 classification, covering 24 out of 25 chapters of diseases (excluding certain conditions originating in the perinatal period). The disease distribution, in decreasing order of average proportion, was as follows: endocrine, nutritional, and metabolic diseases (19.9%); circulatory system diseases (13.7%); respiratory system diseases (13.0%); digestive system diseases (10.5%); musculoskeletal system and connective tissue diseases (9.3%); infectious and parasitic diseases (7.3%). The combined rate of these top 10 diseases accounted for over 50% of the total, with hypertension (17.4%) and Dengue fever (10.4%) being the two most prevalent. Most cases came to the hospital through the outpatient department, with an average rate of 84.3% over the 5 years; about 5% of patients required emergency department services. Most patients participating in health insurance were sponsored by the government (37.4%), followed by those enrolled through household insurance, which has been steadily increasing (36.4%). Conclusions: The disease structure of patients participating in health insurance shares many similarities with the disease structure of developing countries (infectious, respiratory, and digestive diseases), but there is a gradual shift towards non-communicable diseases, reflecting the unique characteristics of a district-level general hospital in Hanoi.